2018
DOI: 10.1097/rct.0000000000000679
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Computed Tomography–Derived Fractional Flow Reserve Based on Structural and Fluid Analysis: Reproducibility of On-site Determination by Unexperienced Observers

Abstract: The CT-derived FFR on-site postprocessing software showed good reproducibility for measurements by inexperienced observers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…The results were reviewed by a radiologist and cardiologist, each of whom had 10 or more years of experience. We previously reported that the correlation coefficient of the CT-FFR value between beginners and skilled analysts increased to 0.83 after specific training with feedback [18]. The inter-observer reproducibility and intra-observer reproducibility have also been found to be favorable among analysts who have trained for a specific time [11], suggesting that results similar to those of this study can be obtained by analysts who undergo specific training.…”
Section: Discussionsupporting
confidence: 77%
“…The results were reviewed by a radiologist and cardiologist, each of whom had 10 or more years of experience. We previously reported that the correlation coefficient of the CT-FFR value between beginners and skilled analysts increased to 0.83 after specific training with feedback [18]. The inter-observer reproducibility and intra-observer reproducibility have also been found to be favorable among analysts who have trained for a specific time [11], suggesting that results similar to those of this study can be obtained by analysts who undergo specific training.…”
Section: Discussionsupporting
confidence: 77%
“…The machine-learning or deep-learning algorithm should be necessary to perform fully automatic CT-FFR measurement to improve the accuracy and to reduce inter-operator variability. However, a previous study reported that automated CT-FFR measurement software using structural and fluid analysis displayed good reproducibility even when the postprocessing was performed by an inexperienced observer given only brief training (32). Lastly, we did not compare the CCTA plus CT-FFR with other gold standard functional imaging i.e.…”
Section: Discussionmentioning
confidence: 94%
“…[20,21] Moreover, the previously cited study also emphasized decreased variabilities in operators receiving face-to-face training [20]. As such in-person training may counter a potential source of variability which has been the incorrect determination of centerline [20,22].…”
Section: Discussionmentioning
confidence: 94%